Fusion of optical coherence tomography and angiography for numerical simulation of hemodynamics in bioresorbable stented coronary artery based on patient-specific model. (31st October 2017) - Huang, Chenxi; Zhou, Yuanhang; Mao, Xiaoxin; Tong, Jianhua; Zhang, Lei; Chen, Fei; Hao, Yongtao
Abstract: Three-dimensional simulations of coronary artery using finite element analysis are considered as effective means to understand the biomechanical properties after the stent was deployed. Bioresorbable vascular scaffolds are new-generation stents used by people. Intravascular optical coherence tomography is an emerging technique for detecting struts. The common 3 D reconstruction methods are using Intravascular Ultrasound (IVUS) or angiographies. However, it loses the details about geometry model. Fusing of optical coherence tomography and angiography to reconstruct the bioresorbable stented coronary artery based on patient-specific mode is an innovative method to reconstruct the high fidelity geometry. This study aimed to use computer-aided design models and computational fluid dynamics research tools to conduct a systematic investigation of blood flow in an isolated artery with realistically deployed coronary stents. Some important hemodynamic factors such as wall shear stress, wall pressure and streamline were calculated. The doctors could evaluate the local hemodynamic alterations within coronary arteries after stent deployment by reconstructing the high-fidelity geometry about each clinical case.